Blood polyphenol concentrations and differentiated thyroid carcinoma in women from the European Prospective Investigation into Cancer and Nutrition (EPIC) study. Issue 1 (6th October 2020) - Zamora-Ros, Raul; Lujan-Barroso, Leila; Achaintre, David; Franceschi, Silvia; Kyrø, Cecilie; Overvad, Kim; Tjønneland, Anne; Truong, Therese; Lecuyer, Lucie; Boutron-Ruault, Marie-Christine; Katzke, Verena; Johnson, Theron S; et al.
ABSTRACT: Background: Polyphenols are natural compounds with anticarcinogenic properties in cellular and animal models, but epidemiological evidence determining the associations of these compounds with thyroid cancer (TC) is lacking. Objectives: The aim of this study was to evaluate the relations between blood concentrations of 36 polyphenols and TC risk in EPIC (the European Prospective Investigation into Cancer and Nutrition). Methods: A nested case–control study was conducted on 273 female cases (210 papillary, 45 follicular, and 18 not otherwise specified TC tumors) and 512 strictly matched controls. Blood polyphenol concentrations were analyzed by HPLC coupled to tandem MS after enzymatic hydrolysis. Results: Using multivariable-adjusted conditional logistic regression models, caffeic acid (ORlog2 : 0.55; 95% CI: 0.33, 0.93) and its dehydrogenated metabolite, 3, 4-dihydroxyphenylpropionic acid (ORlog2 : 0.84; 95% CI: 0.71, 0.99), were inversely associated with differentiated TC risk. Similar results were observed for papillary TC, but not for follicular TC. Ferulic acid was also inversely associated only with papillary TC (ORlog2 : 0.68; 95% CI: 0.51, 0.91). However, none of these relations was significant after Bonferroni correction for multiple testing. No association was observed for any of the remaining polyphenols with total differentiated, papillary, or follicular TC. Conclusions: Blood polyphenol concentrations were mostly not associated with differentiated TC risk in women, although our study raises the possibility that high blood concentrations of caffeic, 3, 4-dihydroxyphenylpropionic, and ferulic acids may be related to a lower papillary TC risk.